Modern Art Museum in the structure of “Cascade” in Yerevan - Роман Селиванов; Грач Шагинян (Проект Байкал)
The creation of a museum of modern art within the structure of the “Cascade” complex in Yerevan is of great importance for the modern development of the city, increasing tourist flow and cultural enlightenment. Due to its location, the museum becomes a communication pedestrian hub between Kentron and Kanaker-Zeytun districts and provides pedestrian accessibility to the outer and inner parts of the complex.